SOSIALISASI DAN PELATIHAN DIGITAL MARKETING PRODUK UMKM DI DESA PUCANGGADING BANDAR KABUPATEN BATANG - Afif, Hasnan; Rahmawati, Anik; Mufidah, Imtiyaz Farras; Jamal, Jamal (PUAN INDONESIA, 2024)
This community service report aims to disseminate information about digital marketing for MSME players. This community service report aims to disseminate information about digital marketing for MSME players. This was carried out by the community service team in Pucanggading Village, Bandar District, Batang Regency, Central Java. Digital marketing is a marketing effort that uses electronic devices or the internet to connect with customers. Socialization of digital marketing in the form of using social media is very important because it can provide knowledge to MSME players regarding the methods and stages of expanding consumer networks through the use of social media in marketing their products so that they can increase competitive advantage for MSMEs themselves. The lack of knowledge of MSME players regarding digital marketing inspired the Community Service team to provide outreach and provide training regarding the use of information and communication technology. If MSMEs understand the importance of digital marketing for their business, it is hoped that they will be motivated to use digital marketing as a means of communication and promotion, and can practice it directly by utilizing social media.